Love's Christmas journey [videorecording (DVD)] - Oke, Janette, 1935-; Borgnine, Ernest, 1917-2012; Williams, JoBeth; Astin, Sean; Shaughnessy, Charles, 1955-; Vaughan, Greg, 1973-; Hall, Natalie, 1988- (20th Century Fox Home Entertainment, 2012)
Still mourning the loss of her family, Ellie agrees to watch her brother's children when he has to leave town. When a fire is set, Ellie works with a handsome deputy to clear a friends name and learns that if she can trust her faith, this Christmas may bring more miracles than she hoped.